Metabolic Syndrome, Obesity, and Drosophila - Bayliak, Maria (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
Metabolic syndrome (MetS) is a cluster of metabolic disturbances increasing a risk of cardiovascular diseases and diabetes 2 types. The main features of MetS include atherogenic dyslipidemia, elevated blood pressure, insulin resistance and elevated glucose levels, a pro-thrombotic state, pro-oxidant and pro-inflammatory states. Excessive consumption of high caloric food and sedentary lifestyle followed by overweight and obesity, as well as aging and stresses are major contributing factors to the MetS development. MeS affects between 10 and 84% of adults depending on the used MetS criteria and increases significantly a risk of cardiovascular diseases, diabetes 2 type and kidney diseases. Patients with metabolic disorders like obesity, diabetes, cardiovascular, and liver disease may have a higher risk of infection of COVID-19 with significantly worse prognosis and outcomes in these patients. In recent years, the fruit fly, Drosophila melanogaster, has been actively used to study human metabolic disorders as a cost-effective and expedient model. Drosophila belongs to insects with full metamorphosis and its life cycle includes four developmental stages: embryo, larva, pupa, and adult flies. Each developmental stage has its own specific advantages and can be used to study metabolic homeostasis. Studies of metabolic disturbances in Drosophila and mammalian models along with humans have demonstrated that flies and small mammalian models have many similarities with humans in basic metabolic functions and share many molecular mechanisms which regulate these metabolic processes. In this paper, we describe the advantages and limitations of Drosophila models of metabolic syndrome and obesity in light of physiological and biochemical similarities and differences between insects and mammals.